Structural characteristics of chasis model for a technology demonstrator - Tuan Noordiyana , Tuan Ismail (2013)
This study presents predictions of structural properties and deformation of vehicle chassis for Automated Guided Vehicle (AGV) that was designed to support at most 15kg work in progress. Finite element analysis involved static loading on vehicle chassis. The scope of this study include identifying location of high stress area and evaluate the torsional stiffness of the chassis. CAD design for the chassis is carried out using Solid works version 2012 and FEA prediction is performed using Comsol multiphysics version 4.2. The result show that the high concentration stress likely to occur at the joints and specific area. The magnitude the stresses depend on the material properties and size of the chassis. High yield strength material will produce less deformation and more rigid chassis structure.